2023
DOI: 10.3390/diagnostics13081396
|View full text |Cite
|
Sign up to set email alerts
|

Salivary ATR-FTIR Spectroscopy Coupled with Support Vector Machine Classification for Screening of Type 2 Diabetes Mellitus

Abstract: The blood diagnosis of diabetes mellitus (DM) is highly accurate; however, it is an invasive, high-cost, and painful procedure. In this context, the combination of ATR-FTIR spectroscopy and machine learning techniques in other biological samples has been used as an alternative tool to develop a non-invasive, fast, inexpensive, and label-free diagnostic or screening platform for several diseases, including DM. In this study, we used the ATR-FTIR tool associated with linear discriminant analysis (LDA) and a supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recently, MG Fernandez-Manteca et al applied many machine learning techniques for the classification of Candida species according to Raman spectra: they also found that the CNN algorithm achieved the greatest accuracy (91%) in the classification of a spectral dataset according to 11 classes [47]. Also, the SVM method was successfully used for the classification of spectra with good accuracy: D. Carvalho Caixeta et al used the ATR-FTIR tool associated with the SVM classifier in order to detect modifications to salivary components to be used as biomarkers for the diagnosis of type 2 diabetes mellitus with an accuracy of 87% [48]. The SVM algorithm was also able to distinguish the Raman spectra of extracellular vesicles in the serum of cancer patients from those of healthy controls with a classification accuracy of 100% when reduced to the spectral frequency range from 1800 to 1940 cm −1 , although the accuracy values significantly decreased to 67% and 57% when the complete Raman spectrum and FTIR spectrum, respectively, were used [49].…”
Section: Dong Et Al Regarding Colon Tissuementioning
confidence: 99%
“…Recently, MG Fernandez-Manteca et al applied many machine learning techniques for the classification of Candida species according to Raman spectra: they also found that the CNN algorithm achieved the greatest accuracy (91%) in the classification of a spectral dataset according to 11 classes [47]. Also, the SVM method was successfully used for the classification of spectra with good accuracy: D. Carvalho Caixeta et al used the ATR-FTIR tool associated with the SVM classifier in order to detect modifications to salivary components to be used as biomarkers for the diagnosis of type 2 diabetes mellitus with an accuracy of 87% [48]. The SVM algorithm was also able to distinguish the Raman spectra of extracellular vesicles in the serum of cancer patients from those of healthy controls with a classification accuracy of 100% when reduced to the spectral frequency range from 1800 to 1940 cm −1 , although the accuracy values significantly decreased to 67% and 57% when the complete Raman spectrum and FTIR spectrum, respectively, were used [49].…”
Section: Dong Et Al Regarding Colon Tissuementioning
confidence: 99%
“…9 It is interesting that based on the FTIR data with ML methods it has been possible to distinguish multiple sclerosis patients from Neuromyelitis optica spectrum disorder and healthy individuals with 100% accuracy, 57 to diagnose pathological thyroid function, 58 it has been possible to distinguish healthy individuals from T1D patients. 59 Differences are sought, but the unifying factor is not found.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that when predictive models for diagnosing the development of oral diseases based on the analysis of the spectral information (the molecular spectra of various analytes) do not usually take into account the effect of associated factors (information about the patients) [ 49 , 50 , 51 , 52 ]. This, in turn, may affect the interpretation of the obtained results.…”
Section: Introductionmentioning
confidence: 99%